2012
DOI: 10.3389/fimmu.2012.00216
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutical Measures to Control Airway Tolerance in Asthma and Lung Cancer

Abstract: Airway tolerance is a specialized immunological surveillance which is activated by the cells of the lung to deal with and distinguish between innocuous and pathogenic inhalants. However, this distinction does not always occur. Airway tolerance is necessary to avoid the development of allergic disorders, such as asthma, which is dominated by a pathological expansion of Th2 and Th17 cells in the airways. By contrast, tumor cells induce tolerogenic factors in their microenvironment to evade T-cell mediated anti-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 96 publications
0
16
0
1
Order By: Relevance
“…Th1 mediated immune responses play a major role for tumour cell rejection. 26 Therefore, we next analyzed Th1 associated factors, expressed by CD4C T-cells in na€ ıve as well as tumour-bearing mice at different time points after lung carcinoma induction. Interestingly, we found that more than 40% of all TbetC CD4C Tcells in the lungs of tumor bearing mice co-expressed Foxp3 and CD25 ( Fig.…”
Section: Accumulation Of Foxp3 Co-expressing Tbet C Cd4 C T-cells In mentioning
confidence: 99%
“…Th1 mediated immune responses play a major role for tumour cell rejection. 26 Therefore, we next analyzed Th1 associated factors, expressed by CD4C T-cells in na€ ıve as well as tumour-bearing mice at different time points after lung carcinoma induction. Interestingly, we found that more than 40% of all TbetC CD4C Tcells in the lungs of tumor bearing mice co-expressed Foxp3 and CD25 ( Fig.…”
Section: Accumulation Of Foxp3 Co-expressing Tbet C Cd4 C T-cells In mentioning
confidence: 99%
“…Antiviral Oas1 genes are inhibited in lung CD4 þ T cells obtained from OVA-sensitized Il17a ( À / À ) mice Aeroallergen sensitization is one of the strongest risk factors for asthma. 33 However, viral infection has also been emerged as a crucial factor in the pathogenesis of this disease. 34 To understand the role of IL-17A in the regulation of different genes that are involved in the response to viral infections, we used a gene array approach in our study.…”
Section: Analysis Of Il17a ( à / à ) Mice In a Murine Model Of Allergmentioning
confidence: 99%
“…Additionally, this panel included two cytokines that are less often investigated in asthma [12]: Interleukin (IL)-1 receptor antagonist (IL-1Ra), an antagonist of IL-1 with antiinflammatory activity [17], and IL-10 able to inhibit pro-inflammatory cytokine synthesis [18,19].…”
Section: Introductionmentioning
confidence: 99%